Multi-layer composite thermal insulation material prepared based on nanofiber membrane and preparation method of multi-layer composite thermal insulation material

Through the multi-layer composite insulation material prepared based on nanofiber membranes, combined with the composite adhesive technology of modified mesoporous nanosilicon dioxide and modified adhesive, the existing fiber insulation materials have poor aging resistance, easy moisture absorption and limited antibacterial properties have been solved, and a high-performance multi-layer composite insulation material has been prepared.

CN119636183AActive Publication Date: 2025-03-18CHANGZHOU YIYUAN MESOPOROUS NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411977976.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In actual applications, existing fiber insulation materials have defects such as poor aging resistance, easy hygroscopic absorption, and limited antibacterial properties, which limit their use scope.

Method used

A multi-layer composite insulation material prepared based on nanofiber membrane is used to prepare a composite adhesive by mixing the modified mesoporous nanosilica and a modified adhesive. The multi-layer nanofiber membrane is composited with composite adhesive to prepare a multi-layer composite insulation material with high mechanical strength, good water resistance, strong antibacteriality and ultraviolet resistance.

Benefits of technology

The mechanical strength improvement, water resistance and antibacterial properties of multi-layer composite insulation materials have been achieved, and the service life of the material has been effectively extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of thermal insulation materials, in particular to a multi-layer composite thermal insulation material prepared on the basis of nanofiber membranes and a preparation method thereof.The preparation method includes the steps that modified mesoporous nano-silica and a modified adhesive are mixed to prepare a composite binder, the composite binder is used for compounding the multiple nanofiber membranes, and the multi-layer composite thermal insulation material is prepared; the preparation method comprises the following steps: preparing a nanofiber membrane by taking polyurethane and mesoporous nano silicon dioxide as solutes and adopting electrostatic spinning; the preparation method comprises the following steps: aminating mesoporous nano silicon dioxide by using 3-aminopropyltriethoxysilane, and then grafting carboxyl-containing ionic liquid; the preparation method comprises the following steps: by taking ethylene glycol diglycidyl ether and 1, 3-propanedithiol as raw materials, synthesizing a polymer macromolecular chain with a side chain containing polyhydroxy, esterifying with carboxyl in 3, 4-dihydroxy phenylacetic acid and a carboxyl-containing ionic liquid structure in a catalytic system of N, N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and then chelating with Zn < 2 + > to prepare the modified adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal insulation materials, and in particular to a multi-layer composite thermal insulation material prepared based on nanofiber membranes and a preparation method thereof. Background Art

[0002] Energy conservation, emission reduction and environmental protection are mainstream topics in today's society. Thermal insulation materials are widely used in civil and military fields such as protective clothing, batteries, pipelines, construction, aerospace, etc. to effectively reduce heat loss during generation, transportation, storage and use.

[0003] Fiber-based thermal insulation materials with low cost, low density, low thermal conductivity, small specific heat capacity, and easy operation have always been favored by the market. However, in actual applications, they still have defects such as poor aging resistance, easy moisture absorption, and limited antibacterial properties, which greatly limit their scope of use. Summary of the invention

[0004] The object of the present invention is to provide a multi-layer composite thermal insulation material prepared based on nanofiber membranes and a preparation method thereof, so as to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a multilayer composite thermal insulation material based on nanofiber membranes comprises the following steps: S1: Mixing modified mesoporous nano-silica, polyurethane and solvent to prepare a spinning solution, and subjecting the mixture to electrospinning to obtain a nanofiber membrane; S2: mixing the modified mesoporous nano-silica and the modified adhesive to obtain a composite adhesive; S3: Compounding multiple layers of nanofiber membranes with a composite adhesive to obtain a multi-layer composite thermal insulation material based on nanofiber membranes.

[0006] Furthermore, the working conditions of the electrospinning treatment were: voltage of 18 kV, spinning solution flow rate of 1.2 mL / h, and receiving distance of 15 cm.

[0007] Furthermore, the spinning solution comprises, by weight, 4-7 parts of modified mesoporous nano-silica, 4-7 parts of polyurethane, and 15-24 parts of solvent.

[0008] Furthermore, the solvent is a mixture of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 2:1.

[0009] Furthermore, the mass ratio of the modified mesoporous nano-silica to the modified adhesive is 7.5-9.5%.

[0010] Furthermore, the preparation of modified mesoporous nano-silica comprises the following steps: (1) Mixing mesoporous nano-silica, 3-aminopropyltriethoxysilane and toluene, adding triethylamine, stirring for 4-5 hours in an oil bath at 108-112°C, cooling, centrifuging, washing, centrifuging and freeze-drying to obtain amino-modified mesoporous nano-silica; (2) Under a nitrogen atmosphere, the amino-modified mesoporous nano-silica and N,N-dimethylformamide are mixed, a carboxyl-containing ionic liquid is added, and ultrasonic stirring is performed. 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is added, and ultrasonic dispersion is performed. The mixture is stirred at 35-45° C. for 10-12 h, and centrifuged, washed, and dried to obtain modified mesoporous nano-silica.

[0011] Further, the preparation of the modified adhesive comprises the following steps: (1) Transfer tetrahydrofuran to -10°C and pre-cool for 15-20 minutes, add ethylene glycol diglycidyl ether, lithium hydroxide, and 1,3-propanedithiol, mix, transfer to a 0°C ice water bath and stir for 6-7 hours, transfer to a -10°C environment, add ethylene glycol diglycidyl ether and keep warm for 1 hour, precipitate with ether, add dichloromethane, centrifuge, add anhydrous ethanol, centrifuge, add dichloromethane, and rotary evaporate to obtain a side chain polyhydroxy polymer; (2) Under a nitrogen atmosphere, the side chain polyhydroxy polymer and N,N-dimethylformamide are mixed, 3,4-dihydroxyphenylacetic acid, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added, and the mixture is stirred in a dark place for 1-2 hours. Then, a carboxyl ionic liquid is added, and the mixture is stirred in a dark place for 22-24 hours. Then, a mixed solution of zinc acetate and N,N-dimethylformamide is added, and the mixture is stirred for 5-10 minutes. The mixture is filtered, precipitated with ether, and washed with anhydrous ethanol and ether for 3-5 times in sequence, and dried to obtain a modified adhesive.

[0012] Furthermore, the mass ratio of the amino-modified mesoporous nano-silica to the carboxyl-containing ionic liquid is 1.5:0.9.

[0013] Furthermore, the mass ratio of the side chain polyhydroxy polymer, 3,4-dihydroxyphenylacetic acid, and the carboxyl group-containing ionic liquid is 2.7:1.6:0.7.

[0014] Further, the preparation of the carboxyl-containing ionic liquid comprises the following steps: A. Under argon protection, methyl 4-chlorobutyrate and N-methylimidazole were mixed, the temperature was raised to 58-62°C and kept for 22-24h, extracted and purified with ether, methanol was added, and dried to obtain 1-methylbutyrate-3-methylimidazole chloride; B. Under argon protection, 1-methyl butyrate-3-methylimidazolium chloride and hydrochloric acid solution were mixed, the temperature was raised to 98-102 ° C and stirred for 1-2h, and the product was purified with anhydrous ether and acetone in turn, and dried to obtain 1-carboxypropyl-3-methylimidazolium chloride; C. Under argon protection, 1-carboxypropyl-3-methylimidazolium chloride, potassium hexafluorophosphate and deionized water are mixed, kept at 68-72°C for 46-48h, kept at 2-4°C until precipitation, filtered, recrystallized and dried to obtain a carboxyl-containing ionic liquid.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a multi-layer composite thermal insulation material based on nanofiber membrane and a preparation method, optimizes the process and components, mixes modified mesoporous nano-silica and modified adhesive to prepare a composite adhesive, and utilizes the composite adhesive to compound the multi-layer nanofiber membrane to prepare a multi-layer composite thermal insulation material with high mechanical strength, good water resistance, strong antibacterial property and UV resistance.

[0016] In the present invention, N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 2:1 are selected as solvents, polyurethane and mesoporous nano-silica are used as solutes, and a nanofiber membrane is prepared by electrostatic spinning. In order to improve the uniformity of the dispersion of the mesoporous nano-silica in the nanofiber membrane, the mesoporous nano-silica is modified, 3-aminopropyltriethoxysilane is used to aminate the mesoporous nano-silica, and then carboxyl-containing ionic liquid is grafted under the action of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, wherein the carboxyl-containing ionic liquid is prepared by reacting N-methylimidazole with methyl 4-chlorobutyrate to obtain 1-methyl butyrate-3-methylimidazole chloride, acidifying to obtain 1-carboxypropyl-3-methylimidazole chloride, and then ion exchange to obtain 1-carboxypropyl-3-methylimidazole hexafluorophosphate, thereby giving the nanofiber membrane excellent waterproofness, UV resistance and antibacterial properties.

[0017] Using ethylene glycol diglycidyl ether and 1,3-propanedithiol as raw materials, a polymer chain containing polyhydroxyl groups in the side chain was synthesized under the catalysis of lithium hydroxide. In the catalyst system of N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the polymer chain was esterified with 3,4-dihydroxyphenylacetic acid and the carboxyl group in the carboxyl group-containing ionic liquid structure. Then, Zn 2+ Chelation is carried out to prepare a modified adhesive with good biocompatibility, enhance the bonding strength and antibacterial properties of the adhesive, and effectively improve the service life of the multi-layer composite thermal insulation material. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0020] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0021] Embodiment 1: A method for preparing a multilayer composite thermal insulation material based on nanofiber membrane, comprising the following steps: S1: Mixing modified mesoporous nano-silica, polyurethane and solvent to prepare a spinning solution, and subjecting the mixture to electrospinning to obtain a nanofiber membrane; The spinning solution is composed of 4 parts of modified mesoporous nano-silica, 4 parts of polyurethane, and 15 parts of solvent in parts by mass; The preparation of modified mesoporous nano-silica includes the following steps: (1) 5 g of mesoporous nano-silica, 9 mL of 3-aminopropyltriethoxysilane, and 40 mL of toluene were mixed, 0.1 g of triethylamine was added, and the mixture was stirred in an oil bath at 108 °C for 5 h, cooled, centrifuged, washed, centrifuged, and freeze-dried to obtain amino-modified mesoporous nano-silica; (2) Under nitrogen atmosphere, 1.5 g of amino-modified mesoporous nano-silica and 20 mL of N,N-dimethylformamide were mixed, 0.9 g of carboxyl-containing ionic liquid was added, ultrasonic stirring was performed, 2.4 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride was added, ultrasonic dispersion was performed, stirring was performed at 35 °C for 12 h, centrifuged, washed, and dried to obtain modified mesoporous nano-silica; The preparation of the carboxyl-containing ionic liquid comprises the following steps: A. Under argon protection, 2.5g 4-chlorobutyric acid methyl ester and 1.5g N-methylimidazole were mixed, the temperature was raised to 58 ° C for 24h, extracted and purified with ether, 10mL methanol was added to dissolve, and the volume ratio of methanol to ethyl acetate was 1:1 as the developing solvent. The mixture was tested by thin layer chromatography and dried to obtain 1-methyl butyrate-3-methylimidazole chloride; B. Under argon protection, 1.1g 1-methyl butyrate-3-methyl imidazole chloride and 0.6g mass concentration of 37% hydrochloric acid solution were mixed, the temperature was raised to 98 ° C and stirred for 2h, and the product was purified by anhydrous ether and acetone in sequence, and methanol was used as a developing solvent. The product was tested by thin layer chromatography and dried to obtain 1-carboxypropyl-3-methyl imidazole chloride; C. Under argon protection, 1 g of 1-carboxypropyl-3-methylimidazolium chloride, 1.2 g of potassium hexafluorophosphate, and 10 mL of deionized water were mixed, heated at 68° C. for 48 h, and heated at 2° C. until precipitation, filtered, recrystallized, and dried to obtain a carboxyl-containing ionic liquid; The solvent is prepared by mixing N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 2:1; The working conditions of the electrospinning treatment were: voltage 18 kV, spinning solution flow rate 1.2 mL / h, receiving distance 15 cm; S2: mixing the modified mesoporous nano-silica and the modified adhesive to obtain a composite adhesive; The mass ratio of modified mesoporous nano-silica and modified binder is 7.5%; The preparation of the modified adhesive comprises the following steps: (1) Transfer 10 mL of tetrahydrofuran to -10 °C and pre-cool for 20 min, add 1.6 g of ethylene glycol diglycidyl ether, 44.3 mg of lithium hydroxide, and 0.9 mL of 1,3-propanedithiol, mix, transfer to a 0 °C ice water bath and stir for 6 h, transfer to a -10 °C environment, add 0.5 g of ethylene glycol diglycidyl ether and keep warm for 1 h, precipitate with ether, add 20 mL of dichloromethane, centrifuge, add 40 mL of anhydrous ethanol, centrifuge, add 20 mL of dichloromethane, and rotary evaporate to obtain a side chain polyhydroxy polymer; (2) Under nitrogen atmosphere, 2.7 g of side chain polyhydroxy polymer and 10 mL of N,N-dimethylformamide were mixed, 1.6 g of 3,4-dihydroxyphenylacetic acid, 4.3 g of N,N-dicyclohexylcarbodiimide and 2.6 g of 4-dimethylaminopyridine were added, and the mixture was stirred in the dark for 1 h. Then, 0.7 g of carboxyl ionic liquid was added, and the mixture was stirred in the dark for 22 h. Then, 0.1 g of zinc acetate and 5 mL of N,N-dimethylformamide were added, and the mixture was stirred for 5 min. The mixture was filtered, precipitated with ether, washed with anhydrous ethanol and ether for 3 times, and dried to obtain a modified adhesive. S3: Compounding multiple layers of nanofiber membranes with a composite adhesive to obtain a multi-layer composite thermal insulation material based on nanofiber membranes.

[0022] Embodiment 2: A method for preparing a multilayer composite thermal insulation material based on nanofiber membrane, comprising the following steps: S1: Mixing modified mesoporous nano-silica, polyurethane and solvent to prepare a spinning solution, and subjecting the mixture to electrospinning to obtain a nanofiber membrane; The spinning solution comprises, by weight, 5 parts of modified mesoporous nano-silica, 5 parts of polyurethane, and 18 parts of solvent; The preparation of modified mesoporous nano-silica includes the following steps: (1) 5 g of mesoporous nano-silica, 9 mL of 3-aminopropyltriethoxysilane, and 40 mL of toluene were mixed, 0.1 g of triethylamine was added, and the mixture was stirred in an oil bath at 110 °C for 4.5 h, cooled, centrifuged, washed, centrifuged, and freeze-dried to obtain amino-modified mesoporous nano-silica; (2) Under a nitrogen atmosphere, 1.5 g of amino-modified mesoporous nano-silica and 20 mL of N,N-dimethylformamide were mixed, 0.9 g of carboxyl-containing ionic liquid was added, and ultrasonic stirring was performed. 2.4 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride was added, and ultrasonic dispersion was performed. The mixture was stirred at 40 °C for 11 h, centrifuged, washed, and dried to obtain modified mesoporous nano-silica. The preparation of the carboxyl-containing ionic liquid comprises the following steps: A. Under argon protection, 2.5g 4-chlorobutyric acid methyl ester and 1.5g N-methylimidazole were mixed, the temperature was raised to 60 ° C for 23h, extracted and purified with ether, 10mL of methanol was added to dissolve, and the volume ratio of methanol to ethyl acetate was 1:1 as the developing solvent. The test was carried out by thin layer chromatography and dried to obtain 1-methyl butyrate-3-methylimidazole chloride; B. Under argon protection, 1.1g 1-methyl butyrate-3-methyl imidazole chloride and 0.6g mass concentration of 37% hydrochloric acid solution were mixed, the temperature was raised to 100 ° C and stirred for 1.5h, rotary evaporation, and the product was purified with anhydrous ether and acetone in sequence, with methanol as the developing solvent, tested by thin layer chromatography, and dried to obtain 1-carboxypropyl-3-methyl imidazole chloride; C. Under argon protection, 1 g of 1-carboxypropyl-3-methylimidazolium chloride, 1.2 g of potassium hexafluorophosphate, and 10 mL of deionized water were mixed, heated at 70° C. for 47 h, and heated at 3° C. until precipitation, filtered, recrystallized, and dried to obtain a carboxyl-containing ionic liquid; The solvent is prepared by mixing N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 2:1; The working conditions of the electrospinning treatment were: voltage 18 kV, spinning solution flow rate 1.2 mL / h, receiving distance 15 cm; S2: mixing the modified mesoporous nano-silica and the modified adhesive to obtain a composite adhesive; The mass ratio of modified mesoporous nano-silica and modified binder is 8.5%; The preparation of the modified adhesive comprises the following steps: (1) Transfer 10 mL of tetrahydrofuran to -10 °C and pre-cool for 20 min, add 1.6 g of ethylene glycol diglycidyl ether, 44.3 mg of lithium hydroxide, and 0.9 mL of 1,3-propanedithiol, mix, transfer to a 0 °C ice water bath and stir for 6.5 h, transfer to a -10 °C environment, add 0.5 g of ethylene glycol diglycidyl ether and keep warm for 1 h, precipitate with ether, add 20 mL of dichloromethane, centrifuge, add 40 mL of anhydrous ethanol, centrifuge, add 20 mL of dichloromethane, and evaporate to obtain a side chain polyhydroxy polymer; (2) Under a nitrogen atmosphere, 2.7 g of a side chain polyhydroxy polymer and 10 mL of N,N-dimethylformamide were mixed, and 1.6 g of 3,4-dihydroxyphenylacetic acid, 4.3 g of N,N-dicyclohexylcarbodiimide, and 2.6 g of 4-dimethylaminopyridine were added. After stirring in the dark for 1.5 h, 0.7 g of a carboxyl ionic liquid was added. After stirring in the dark for 23 h, a mixed solution of 0.1 g of zinc acetate and 5 mL of N,N-dimethylformamide was added. The mixture was stirred for 8 min, filtered, precipitated with ether, washed with anhydrous ethanol and ether for 4 times, and dried to obtain a modified adhesive. S3: Compounding multiple layers of nanofiber membranes with a composite adhesive to obtain a multi-layer composite thermal insulation material based on nanofiber membranes.

[0023] Embodiment 3: A method for preparing a multilayer composite thermal insulation material based on nanofiber membrane, comprising the following steps: S1: Mixing modified mesoporous nano-silica, polyurethane and solvent to prepare a spinning solution, and subjecting the mixture to electrospinning to obtain a nanofiber membrane; The spinning solution comprises, by weight, 7 parts of modified mesoporous nano-silica, 7 parts of polyurethane, and 24 parts of solvent; The preparation of modified mesoporous nano-silica includes the following steps: (1) 5 g of mesoporous nano-silica, 9 mL of 3-aminopropyltriethoxysilane, and 40 mL of toluene were mixed, 0.1 g of triethylamine was added, and the mixture was stirred in an oil bath at 112 °C for 4 h, cooled, centrifuged, washed, centrifuged, and freeze-dried to obtain amino-modified mesoporous nano-silica; (2) Under a nitrogen atmosphere, 1.5 g of amino-modified mesoporous nano-silica and 20 mL of N,N-dimethylformamide were mixed, 0.9 g of carboxyl-containing ionic liquid was added, and ultrasonic stirring was performed. 2.4 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride was added, and ultrasonic dispersion was performed. The mixture was stirred at 45 °C for 10 h, centrifuged, washed, and dried to obtain modified mesoporous nano-silica. The preparation of the carboxyl-containing ionic liquid comprises the following steps: A. Under argon protection, 2.5g 4-chlorobutyric acid methyl ester and 1.5g N-methylimidazole were mixed, the temperature was raised to 62 ° C for 22h, extracted and purified with ether, 10mL methanol was added to dissolve, and the volume ratio of methanol to ethyl acetate was 1:1 as the developing solvent. The test was carried out by thin layer chromatography and dried to obtain 1-methyl butyrate-3-methylimidazole chloride; B. Under argon protection, 1.1g 1-methyl butyrate-3-methyl imidazole chloride and 0.6g mass concentration of 37% hydrochloric acid solution were mixed, the temperature was raised to 102 ° C and stirred for 1h, and the product was purified by anhydrous ether and acetone in sequence, and methanol was used as a developing solvent. The product was tested by thin layer chromatography and dried to obtain 1-carboxypropyl-3-methyl imidazole chloride; C. Under argon protection, 1 g of 1-carboxypropyl-3-methylimidazolium chloride, 1.2 g of potassium hexafluorophosphate, and 10 mL of deionized water were mixed, heated at 72° C. for 46 h, and heated at 4° C. until precipitation, filtered, recrystallized, and dried to obtain a carboxyl-containing ionic liquid; The solvent is prepared by mixing N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 2:1; The working conditions of the electrospinning treatment were: voltage 18 kV, spinning solution flow rate 1.2 mL / h, receiving distance 15 cm; S2: mixing the modified mesoporous nano-silica and the modified adhesive to obtain a composite adhesive; The mass ratio of modified mesoporous nano-silica and modified binder is 9.5%; The preparation of the modified adhesive comprises the following steps: (1) Transfer 10 mL of tetrahydrofuran to -10 °C and pre-cool for 20 min, add 1.6 g of ethylene glycol diglycidyl ether, 44.3 mg of lithium hydroxide, and 0.9 mL of 1,3-propanedithiol, mix, transfer to a 0 °C ice water bath and stir for 7 h, transfer to a -10 °C environment, add 0.5 g of ethylene glycol diglycidyl ether and keep warm for 1 h, precipitate with ether, add 20 mL of dichloromethane, centrifuge, add 40 mL of anhydrous ethanol, centrifuge, add 20 mL of dichloromethane, and evaporate to obtain a side chain polyhydroxy polymer; (2) Under a nitrogen atmosphere, 2.7 g of a side chain polyhydroxy polymer and 10 mL of N,N-dimethylformamide were mixed, and 1.6 g of 3,4-dihydroxyphenylacetic acid, 4.3 g of N,N-dicyclohexylcarbodiimide, and 2.6 g of 4-dimethylaminopyridine were added. After stirring in the dark for 2 h, 0.7 g of a carboxyl ionic liquid was added. After stirring in the dark for 24 h, a mixed solution of 0.1 g of zinc acetate and 5 mL of N,N-dimethylformamide was added. The mixture was stirred for 10 min, filtered, precipitated with ether, washed with anhydrous ethanol and ether for 5 times, and dried to obtain a modified adhesive. S3: Compounding multiple layers of nanofiber membranes with a composite adhesive to obtain a multi-layer composite thermal insulation material based on nanofiber membranes.

[0024] Comparative Example 1: Taking Example 3 as the control group, the modified mesoporous nano-silica was replaced by mesoporous nano-silica, and the other processes were normal.

[0025] Comparative Example 2: Taking Example 3 as the control group, the modified adhesive was replaced by polyurethane (Henkel Loctite UR3370GRAY), and the other processes were normal.

[0026] Comparative Example 3: Example 3 was used as a control group, in which no carboxyl group-containing ionic liquid was prepared, and other processes were normal.

[0027] In the embodiment and the comparative example: the thickness of the nanofiber membrane is 20 μm, the thickness of the composite binder coated on the nanofiber membrane is 5 μm, and the nanofiber membrane has 5 layers.

[0028] Sources of raw materials used (for demonstration purposes only): Polyurethane TPUA85P4441: Huntsman; Mesoporous nanosilica (20nm): Changzhou Yiyuan Mesoporous New Materials Co., Ltd.; N-methylimidazole BD4522: Hubei Baidu Chemical Co., Ltd.; 3-aminopropyltriethoxysilane A107147, triethylamine T103285, N,N-dimethylformamide D111999, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride E106172, 4-chlorobutyric acid methyl ester C108118, hexadecene Potassium fluorophosphate P104055, tetrahydrofuran T103263, ethylene glycol diglycidyl ether G132841, lithium hydroxide L106770, 1,3-propanedithiol P100845, 3,4-dihydroxyphenylacetic acid D106475, N,N-dicyclohexylcarbodiimide D106074, 4-dimethylaminopyridine D109207, zinc acetate Z110777: Aladdin reagent; toluene, ether, methanol, ethyl acetate, acetone, analytical grade: Sinopharm reagent.

[0029] Performance test: Test the materials prepared in the examples and comparative examples: Thermal conductivity: tested by thermal conductivity tester; Antibacterial persistence: the sample was washed with standard water 10 times, and then tested by plate method, with Staphylococcus aureus as the test strain; UV resistance: irradiated with 365nm ultraviolet light for 72 hours, and the antibacterial property was tested again. If the antibacterial change rate compared with the initial antibacterial rate was between 0-1% and 1%, it was qualified, otherwise it was unqualified; Water resistance: soaked in 50℃ deionized water for 72 hours, and observed whether there was bubbling, separation and other phenomena. If there was no bubbling, separation and other phenomena, it was qualified, otherwise it was unqualified; the results are shown in Table 1; Table 1

[0030] The present invention provides a multi-layer composite thermal insulation material based on nanofiber membrane and a preparation method, optimizes the process and components, mixes modified mesoporous nano-silica and modified adhesive to prepare a composite adhesive, and utilizes the composite adhesive to compound the multi-layer nanofiber membrane to prepare a multi-layer composite thermal insulation material with high mechanical strength, good water resistance, strong antibacterial property and UV resistance.

[0031] By comparing Example 3 with Comparative Example 1 and Comparative Example 3, it can be seen that in the present invention, N,N-dimethylformamide and tetrahydrofuran with a volume ratio of 2:1 are selected as solvents, polyurethane and mesoporous nano-silica are used as solutes, and nanofiber membranes are prepared by electrospinning. In order to improve the uniformity of dispersion of mesoporous nano-silica in the nanofiber membrane, the mesoporous nano-silica is modified, and the mesoporous nano-silica is aminated with 3-aminopropyltriethoxysilane, and then grafted with a carboxyl-containing ionic liquid under the action of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, wherein the carboxyl-containing ionic liquid is N-methylimidazole as a raw material, and reacts with 4-chlorobutyric acid methyl ester to obtain 1-methyl butyrate-3-methylimidazole chloride, and after acidification, 1-carboxypropyl-3-methylimidazole chloride is obtained, and then ion exchange is performed to obtain 1-carboxypropyl-3-methylimidazole hexafluorophosphate, thereby giving the nanofiber membrane excellent waterproofness, UV resistance and antibacterial properties.

[0032] By comparing Example 3 with Comparative Examples 2 and 3, it can be seen that ethylene glycol diglycidyl ether and 1,3-propylene glycol mercaptan are used as raw materials to synthesize a polymer chain containing polyhydroxyl groups in the side chain under the catalysis of lithium hydroxide, and esterification occurs with 3,4-dihydroxyphenylacetic acid and the carboxyl group in the carboxyl group-containing ionic liquid structure in the N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine catalyst system, and then Zn 2+ Chelation is carried out to prepare a modified adhesive with good biocompatibility, enhance the bonding strength and antibacterial properties of the adhesive, and effectively improve the service life of the multi-layer composite thermal insulation material.

[0033] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a multilayer composite thermal insulation material based on nanofiber membrane, characterized in that: The following steps are involved: S1: Mixing modified mesoporous nano-silica, polyurethane and solvent to prepare a spinning solution, and subjecting the mixture to electrospinning to obtain a nanofiber membrane; S2: mixing the modified mesoporous nano-silica and the modified adhesive to obtain a composite adhesive; S3: Compounding multiple layers of nanofiber membranes with a composite adhesive to obtain a multi-layer composite thermal insulation material based on nanofiber membranes.

2. The method for preparing a multilayer composite thermal insulation material based on nanofiber membrane according to claim 1, characterized in that: The working conditions of the electrospinning treatment were: voltage of 18 kV, spinning solution flow rate of 1.2 mL / h, and receiving distance of 15 cm.

3. The method for preparing a multilayer composite thermal insulation material based on nanofiber membrane according to claim 1, characterized in that: The spinning solution comprises, by weight, 4-7 parts of modified mesoporous nano-silica, 4-7 parts of polyurethane, and 15-24 parts of solvent.

4. The method for preparing a multilayer composite thermal insulation material based on nanofiber membrane according to claim 1, characterized in that: The solvent is prepared by mixing N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 2:

1.

5. The method for preparing a multilayer composite thermal insulation material based on nanofiber membrane according to claim 1, characterized in that: The mass ratio of the modified mesoporous nano-silica to the modified adhesive is 7.5-9.5%.

6. The method for preparing a multilayer composite thermal insulation material based on nanofiber membrane according to claim 1, characterized in that: The preparation of modified mesoporous nano-silica includes the following steps: (1) Mixing mesoporous nano-silica, 3-aminopropyltriethoxysilane and toluene, adding triethylamine, stirring for 4-5 hours in an oil bath at 108-112°C, cooling, centrifuging, washing, centrifuging and freeze-drying to obtain amino-modified mesoporous nano-silica; (2) Under a nitrogen atmosphere, the amino-modified mesoporous nano-silica and N,N-dimethylformamide are mixed, a carboxyl-containing ionic liquid is added, and ultrasonic stirring is performed. 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is added, and ultrasonic dispersion is performed. The mixture is stirred at 35-45° C. for 10-12 h, and centrifuged, washed, and dried to obtain modified mesoporous nano-silica.

7. The method for preparing a multilayer composite thermal insulation material based on nanofiber membrane according to claim 1, characterized in that: The preparation of the modified adhesive comprises the following steps: (1) Transfer tetrahydrofuran to -10°C and pre-cool for 15-20 minutes, add ethylene glycol diglycidyl ether, lithium hydroxide, and 1,3-propanedithiol, mix, transfer to a 0°C ice water bath and stir for 6-7 hours, transfer to a -10°C environment, add ethylene glycol diglycidyl ether and keep warm for 1 hour, precipitate with ether, add dichloromethane, centrifuge, add anhydrous ethanol, centrifuge, add dichloromethane, and rotary evaporate to obtain a side chain polyhydroxy polymer; (2) Under a nitrogen atmosphere, the side chain polyhydroxy polymer and N,N-dimethylformamide are mixed, 3,4-dihydroxyphenylacetic acid, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added, and the mixture is stirred in a dark place for 1-2 hours. Then, a carboxyl ionic liquid is added, and the mixture is stirred in a dark place for 22-24 hours. Then, a mixed solution of zinc acetate and N,N-dimethylformamide is added, and the mixture is stirred for 5-10 minutes. The mixture is filtered, precipitated with ether, and washed with anhydrous ethanol and ether for 3-5 times in sequence, and dried to obtain a modified adhesive.

8. The method for preparing a multi-layer composite thermal insulation material based on nanofiber membrane according to claim 7, characterized in that: The mass ratio of the side chain polyhydroxy polymer, 3,4-dihydroxyphenylacetic acid and the carboxyl group-containing ionic liquid is 2.7:1.6:0.

7.

9. The method for preparing a multilayer composite thermal insulation material based on nanofiber membrane according to claim 6 or 7, characterized in that: The preparation of the carboxyl-containing ionic liquid comprises the following steps: A. Under argon protection, methyl 4-chlorobutyrate and N-methylimidazole were mixed, the temperature was raised to 58-62°C and kept for 22-24h, extracted and purified with ether, methanol was added, and dried to obtain 1-methylbutyrate-3-methylimidazole chloride; B. Under argon protection, 1-methyl butyrate-3-methylimidazolium chloride and hydrochloric acid solution were mixed, the temperature was raised to 98-102 ° C and stirred for 1-2h, and the product was purified with anhydrous ether and acetone in turn, and dried to obtain 1-carboxypropyl-3-methylimidazolium chloride; C. Under argon protection, 1-carboxypropyl-3-methylimidazolium chloride, potassium hexafluorophosphate and deionized water are mixed, kept at 68-72°C for 46-48h, kept at 2-4°C until precipitation, filtered, recrystallized and dried to obtain a carboxyl-containing ionic liquid.

10. A multi-layer composite thermal insulation material prepared based on nanofiber membrane, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Hydroxyl functional ionic liquid and preparation method thereof

    CN114349706A

  • Thermal insulation nanofiber membrane material and preparation method thereof

    CN117901496A

  • Medical antibacterial bedding fabric and preparation process thereof

    CN118186618A